*NEG NEG. Issue 1 (24th May 2018) - Collins, Chris
Abstract : I argue that there is a grammatical (non-semantic) constraint in English that prohibits double negation, dubbed *NEG NEG. I adduce a range of structures to illustrate this constraint, and show that apparent counter-examples are not double negation.